Conference Report: 60th American Society for MS Conference on MS and Allied Topics. (September 2012) - Touboul, David; Seyer, Alexandre; Becher, François
The 60th American Society for Mass Spectrometry (ASMS) Conference on MS and Allied Topics was held in May 2012 at Vancouver in Canada. This international congress is the largest forum exclusively dedicated to MS through its diverse aspects: fundamental, method development and applications to biomolecules. This 4-day conference is also highly appreciated for discussion with the MS manufacturers presenting their latest instrumental developments.